Analisis Sentimen Masyarakat Terhadap Isu Migrasi Rohingya Ke Indonesia - Kurniasih, Ulfa; Suseno, Akrim Teguh (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The phenomenon of the Rohingya refugee exodus is something that attracts a lot of public interest on social media. This study aims to see how the public represents the phenomenon of the presence of Rohingya refugees in Indonesia on X social media with the Decision tree 5.0 algorithm and Naive bayes with the keyword "rohingya". The results of the study showed that negative sentiment is still dominant on X social media with an average of 49.5%, positive sentiment 18.5% and neutral sentiment 27%. For validity testing using the K-Fold Validation method, it shows that the naïve Bayes algorithm has a better level of accuracy with an accuracy level of 83% while the decision tree only has an accuracy level of 78%. The results of the study indicate that Indonesian people through X social media still tend to give a negative attitude towards the presence of Rohingya refugees in Indonesia.